Analisis komprehensif buku teks Akidah Akhlak Madrasah Ibtidaiyah kelas V berdasarkan kurikulum Merdeka - El Khaira, Nabilah; Tumin (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
This research aims to analyze the feasibility of the Akidah Akhlak textbook as a teaching material for Islamic Religious Education in madrasahs, specifically in terms of content components, language, presentation, and learning evaluation. The Akidah Akhlak textbook plays a strategic role in shaping the understanding of faith and instilling noble moral values in students, so the quality of the book used needs to be systematically examined. This research uses a qualitative approach with content analysis method on the Akidah Akhlak book used in Madrasah Ibtidaiyah. Data collection techniques were carried out thru documentation studies by examining the alignment of the material with the curriculum, clarity of language, systematic presentation, and the forms of evaluation presented in the book. The research results indicate that, in general, the Akidah Akhlak book has met the feasibility criteria as a teaching material, both in terms of the alignment of the material with basic competencies, the use of communicative and educational language, and systematic and contextual presentation. However, several limitations were still found, particularly in the depth of certain materials, simplification of attitude assessments, and the suboptimal variation of learning evaluations. Therefore, this Akidah Akhlak book is suitable to be used as the main learning resource, with the note that strengthening the role of teachers and developing learning strategies are necessary so that the goal of character building for students can be optimally achieved. Abstrak Penelitian ini bertujuan untuk menganalisis kelayakan buku teks Akidah Akhlak sebagai bahan ajar Pendidikan Agama Islam di madrasah, khususnya ditinjau dari komponen isi, kebahasaan, penyajian, dan evaluasi pembelajaran. Buku teks Akidah Akhlak memiliki peran strategis dalam membentuk pemahaman keimanan serta menanamkan nilai-nilai akhlak mulia pada peserta didik, sehingga kualitas buku yang digunakan perlu dikaji secara sistematis. Penelitian ini menggunakan pendekatan kualitatif dengan metode analisis isi (content analysis) terhadap buku Akidah Akhlak yang digunakan di Madrasah Ibtidaiyah. Teknik pengumpulan data dilakukan melalui studi dokumentasi dengan mencermati kesesuaian materi dengan kurikulum, kejelasan bahasa, sistematika penyajian, serta bentuk evaluasi yang disajikan dalam buku. Hasil penelitian menunjukkan bahwa secara umum buku Akidah Akhlak telah memenuhi kriteria kelayakan sebagai bahan ajar, baik dari segi kesesuaian materi dengan kompetensi dasar, penggunaan bahasa yang komunikatif dan edukatif, maupun penyajian yang sistematis dan kontekstual. Namun demikian, masih ditemukan beberapa keterbatasan, terutama pada pendalaman materi tertentu, penyederhanaan penilaian sikap, serta belum optimalnya variasi evaluasi pembelajaran. Oleh karena itu, buku Akidah Akhlak ini layak digunakan sebagai sumber belajar utama, dengan catatan diperlukan penguatan peran guru dan pengembangan strategi pembelajaran agar tujuan pembentukan karakter peserta didik dapat tercapai secara optimal.